Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1037/int0000206
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualizing racism through a systemic trauma lens: Impacts on Black college students.

Abstract: Systemic trauma is a perspective that extends the traditionally narrow view of trauma into a framework that includes systems, institutions, and contextual factors into the conceptualization of trauma. This framework captures the effects of racism, systemic barriers (e.g., racial climate, cultural mistrust, stereotype threat), and contextual factors (e.g., technology, social media) as these mechanisms inform experiences of trauma for marginalized populations. Some scholars argue that there is a need for researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 65 publications
2
19
0
Order By: Relevance
“…The results underscored the association of group-based discrimination like racism and COVID-19 different stressors and infection (e.g., Khazanchi et al, 2020). They replicated a rich literature on the mental health effects of racism (e.g., Williams et al, 2021). They confirmed and expanded on previous studies that found that experiencing even subtle racial discrimination had adverse cognitive effects (Ozier et al, 2019;Zahodne et al, 2016).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The results underscored the association of group-based discrimination like racism and COVID-19 different stressors and infection (e.g., Khazanchi et al, 2020). They replicated a rich literature on the mental health effects of racism (e.g., Williams et al, 2021). They confirmed and expanded on previous studies that found that experiencing even subtle racial discrimination had adverse cognitive effects (Ozier et al, 2019;Zahodne et al, 2016).…”
Section: Discussionsupporting
confidence: 78%
“…The present study did not test for dissociation and psychotic symptoms; however, there is strong empirical evidence that ethnic minority position and migrant status are risk factors for psychotic symptoms (for review and meta-analysis see, Leaune et al, 2019). There is empirical evidence of the higher suicidality in immigrants/refugees (for meta-analysis, see Amiri, 2020) and lesbian, gay, bisexual, transgender, and queer [LGBTQ] (for meta-analysis, see Williams et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Few practitioners identify as black women, and thus, nonblack and male providers must be culturally competent and comfortable with offering safe, affirming, and non-judgmental spaces for black women to share and process their experiences (Bryant-Davis 2007; Comas-Dı ´az, Hall, and Neville 2019). Second, healing from gendered racial microaggressions will require the use of culturally appropriate treatment (Sue and Sue 2015; T. R. Williams, Walker, and Wyatt 2022). In other words, clinicians' treatment approach must address cultural or other diversity factors that inform black women's experiences.…”
Section: Implications For Clinical Practicementioning
confidence: 99%
“…First, the relatively small sample of monoracial Black and biracial Black students limit its generalizability and our ability to probe diversity within the monoracial Black and biracial Black groups. Exploring how factors related to ethnic identity [ 31 ], skin tone [ 37 ], community support [ 38 ], and others [ 39 ], moderate the impact of exposure to police brutality on race-based trauma symptoms and well-being will be critical to better understand the diversity of Black student experiences. In terms of generalizability, it is also worth acknowledging the unique geo-political context of the current institution relative to other small private institutions.…”
Section: Limitations and Future Researchmentioning
confidence: 99%